Sanace objektu Villa Mirabella - Janovská, Nela (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Práce řeší sanaci a statické zajištění historického objektu z 18. století na základě zjištěných poruch během prohlídky na místě samém a ze zaslaných podkladů. Paralelně se statickým zajištěním objektu byla provedena studie možného zřízení nového technického zázemí pod objektem včetně technologických postupů provádění. Práce obsahuje detailní výpočet zatížení, návrh sanace objektu, návrh a posouzení vybraných částí nového technického zázemí a výkresovou dokumentaci ke všem provedeným výpočtům a návrhům.

The work solves the remediation and static securing of the historical building from the 18th century on the basis of detected defects during the site inspection itself and from the sent supporting documents. Parallel to the static securing of the object, a study was carried out on the possible establishment of a new technical background under the object including the technological procedures for implementation. The work includes a detailed load calculation, the design of the object remediation, the design and assessment of selected parts of the new technical background, and mechanical drawings for all performed calculations and designs.
Static security of Villa Mirabella
Keywords: sanace; prohlídka; zdivo; pevnost; beton; konstrukce; předpjatý beton; stropní konstrukce; remediation; inspection; masonry; strength; concrete; construction; prestressed concrete; ceiling construction